Synergistic Effect of Nitrogen Fertilizer Management on Rice Productivity and Quality - Yongkang Teng; Rongjie Chen; Meng Guo; Xianguan Chen; Min Jiang (Agronomy)
This study investigated how nitrogen fertilizer management influences the yield and grain quality of two rice cultivars, Nanjing 9108 (a late-maturing medium japonica) and Ming 1 Youzhenzhan (a three-line indica hybrid). Three field experiments were conducted to assess different nitrogen application strategies, including total nitrogen reduction, panicle-stage nitrogen reduction, and substitution of chemical fertilizer with compound fertilizer. The experiments analyzed changes in rice nitrogen uptake and transport efficiency, yield and its components, and quality and its components under different nitrogen application treatments, and fitted a function based on the effect of total nitrogen fertilizer on quality. Taking into account four quality indicators and ensuring yield reduction is less than 30%, replacing 100% chemical fertilizer with compound fertilizer in Nanjing 9108 was the optimal strategy for significantly improving quality. Reducing panicle fertilizer by 50% or omitting it also significantly improved quality. Replacing chemical fertilizers with 50% compound fertilizer also maintained nutritional quality. Reducing total nitrogen fertilizer by 25% in Ming 1 Youzhenzhan was the optimal strategy for significantly enhancing quality. Replacing chemical fertilizer with 100% compound fertilizer significantly improved quality. Reducing panicle fertilizer by 50% and substituting 50% of chemical fertilizer with compound fertilizer also significantly improved quality. Taking into account the synergistic effects of nitrogen application measures on rice yield and quality, the performance of the two rice varieties is not identical. The results showed that nitrogen fertilizer management significantly affected both yield and quality, with responses varying between the two varieties. But the two varieties can ensure optimal quality under yield conditions by reducing panicle fertilizer application by 50% and replacing chemical fertilizers with compound fertilizers.